Tensile Bond Strength of Three Custom-made Tooth-Colored Implant Superstructures to Titanium Inserts - Mitra Zirak; Mahroo Vojdani; Amir Ali Reza Khaledi; Mitra Farzin (Shiraz University of Medical Sciences, 2019)
Statement of the Problem: Hybrid abutments are made of a titanium implant insert and a ceramic component. The tensile bond strength between the titanium implant insert and the ceramic component is not still clearly known. Purpose: This in vitro study aimed to compare the tensile bond strength of the titanium insert to ceramic components made of milled lithium disilicate, milled zirconia, and pressable lithium disilicate. Materials and Method: To standardize the shape and dimension of the ceramic components, a single computer-aided design/computer assisted manufacturing (CAD/CAM) superstructure was designed with Dental Designer software. Based on this model, CAD milled zirconia (Zr), CAD milled Lithium disilicate (CAD-LD) and heat-pressed lithium-disilicate (H-LD) superstructures were fabricated (n=10 per group). They were bonded to the titanium inserts by using self-adhesive resin cement. The prepared superstructure-titanium insert complexes (hybrid abutments) were screwed into the implants with 35 Ncm torque. The tensile bond strength of the ceramic superstructures to the titanium inserts were recorded by the universal testing machine with a crosshead speed of 2 mm/min. The data were analyzed by using one-way ANOVA and Tamhane post-hoc test (p< 0.05). Results: The mean±SD of tensile bond strength was 328.50±30.4 N in CAD-LD, 257.30±23.8 N in H-LD, and 242.20±21.2 N in Zr groups. One-way ANOVA revealed the groups significantly different in terms of the tensile bond strength (p< 0.001). Tamhane post-hoc test showed a significant difference between the CAD-LD and the two other groups (p<0.001); however, no statistically significant difference was detected between the H-LD and Zr groups (p= 0.39). Conclusion: It can be concluded that the CAD-LD has higher bond strength to titanium insert compared with the H-LD and Zr groups. Therefore, they might be clinically more beneficial in high-esthetic areas.